Investigation of blood culture-negative early prosthetic valve endocarditis reveals high prevalence of fungi. Issue 10 (11th November 2009) - Thuny, Franck; Fournier, Pierre-Edouard; Casalta, Jean-Paul; Gouriet, Frédérique; Lepidi, Hubert; Riberi, Alberto; Collart, Frédéric; Habib, Gilbert; Raoult, Didier
Abstract : Context: Early prosthetic valve endocarditis is a deadly disease and blood cultures remain negative in 14–30% of cases. Objectives: To analyse the clinical and microbiological profile of patients with blood culture-negative (BCN) early prosthetic valve endocarditis (PVE) in order to define the most appropriate empiric treatment. Design, Setting and Participants: From June 2001 to February 2009, a prospective multimodal strategy incorporating serological, molecular and histopathological assays was performed in all the samples referred to the laboratory for a suspicion of blood culture-negative endocarditis (BCNE) from France and abroad (n=718). A total of 31 patients with BCN early PVE was identified. Their microbiological profile was compared with that of 22 patients with blood culture-positive (BCP) early PVE and 628 patients with community-acquired BCNE identified during the same period. Results: A pathogen was identified in 10 patients (32%) with BCN early PVE. Fungi were the most common pathogens identified, being found in 16% versus 4.5% in the case of PBC early PVE and 0.5% in community-acquired BCNE (p<0.001). The global microbiological profile of BCN early PVE differed strongly from that of PBC early PVE and community-acquired BCNE. A higher rate of microbiological diagnosis was obtained in patients who underwent surgery (9/21 (43%) vs 1/10 (10%), p=0.07) and an increased rate of recurrences was observed when a pathogen could not be identified (9/21 (43%) vs 1/10 (10%), p=0.07). Conclusions: BCN early PVE exhibits specific aetiologies as fungi are the most frequent pathogens identified. Therefore, fungi should be investigated particularly by molecular methods on surgical specimens and an antifungal drug might be added to the empiric treatment.